Self-reported factors associated with community ambulation after stroke: The Canadian Longitudinal Study on Aging. - Ruth Barclay; Sandra C Webber; Jacquie Ripat; Scott Nowicki; Robert Tate (PLoS ONE, 2024)
Community ambulation is frequently limited for people with stroke. It is, however, considered important to people with stroke. The objectives were to identify factors associated with self-reported community ambulation in Canadians aged 45+ with stroke and to identify factors associated with community ambulation specific to Canadian males and to Canadian females with stroke. Data were utilized from the Canadian Longitudinal Study on Aging Tracking Cohort. Multivariate logistic regression models were developed for community ambulation. Mean age was 68 (SE 0.5) years (45% female). In the final community ambulation model (n = 855), factors associated with being less likely to 'walk outdoors sometimes or often' included difficulty or being unable to walk 2-3 blocks (decreased endurance) vs. no difficulty. Being more likely to walk outdoors was associated with 'better weather' months and being 55-64 years of age vs 75-85. Differences were noted between the models of only males and only females. Decreased walking endurance is associated with a decreased likelihood of walking in the community-a factor that can be addressed by rehabilitation professionals and in community based programs.